2021
DOI: 10.3390/su13116295
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Solar Energy towards Efficient and Sustainable Energy

Abstract: Conventional energy resources are not climate sustainable. Currently, engineers and scientists are looking for sustainable energy solutions influenced by climate change. A wide variety of sustainable natural energy resources are available, but they require technical solutions for their implementation. The general trend in energy research is based on renewable resources, amongst which solar energy stands out, being the most mature and widely accepted. In this paper, the current state of the sustainable energy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…The main principle of solar thermal systems is the conversion of solar energy into useful energy using thermal collectors [23]. In most cases solar water heating systems are connected to the existing home water heating system using the capacity of the existing boiler in the system [24]. There are systems that have a low hot water storage performance [25].…”
Section: Methodsmentioning
confidence: 99%
“…The main principle of solar thermal systems is the conversion of solar energy into useful energy using thermal collectors [23]. In most cases solar water heating systems are connected to the existing home water heating system using the capacity of the existing boiler in the system [24]. There are systems that have a low hot water storage performance [25].…”
Section: Methodsmentioning
confidence: 99%
“…Researchers are crucial to the advancement of technology. In nine main fields of solar energy sustainable development, 11,848 writers from 131 countries are working (Novas et al, 2021). Europe has 4080 researchers, the most of any continent, whereas Africa has the least contribution in the field of research, with several countries making no contribution at all (Garcia et al, 2020;Novas et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to these reasons, it is necessary to look at some other alternative green sources for autonomous self-powered sensors. Although, harvesting electrical energy from the sun is a matured and well-accepted technique, [17][18][19] this technique has a limitation that it remains functional only in the presence of sunlight. Recently scientific explorations showed that plants may become a potential source of bioenergy that is not only renewable but also sustainable and cheap [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%